Overcoming the cohesive zone limit in composites delamination: modeling with slender structural elements and higher‐order adaptive integration. (27th September 2020) - Russo, Raffaele; Chen, Boyang
Summary: Cohesive element (CE) is a well‐established finite element for fracture, widely used for the modeling of delamination in composites. However, an extremely fine mesh is usually needed to resolve the cohesive zone, making CE‐based delamination analysis computationally prohibitive for applications beyond the scale of lab coupons. In this work, a new CE‐based method of modeling delamination in composites is proposed to overcome this cohesive zone limit on the mesh density. The proposed method makes use of slender structural elements for the plies, a compatible formulation with adaptive higher‐order integration for the CEs, and the corotational formulation for geometrically nonlinear analysis. The proposed method is verified and validated on the classical benchmark problems of Mode I, II, mixed‐mode delamination, a buckling‐induced delamination problem and a double‐delamination problem. The results show that elements much larger than the cohesive zone length can be used while retaining accuracy.